Design and application of an adhesive ophthalmic drug delivery device (一种粘贴式眼科受水器的设计与应用) - JIA Tingting (贾婷婷); SHI Jinghua (史静华); GUO Lixia (郭丽霞); XU Yuanle (许远乐) (中西医结合护理)
Irrigation of the conjunctival sac is an emergency treatment if there has been chemical injury to the eye, and the ocular drug delivery device is an essential tool for irrigation. This paper introduced the design and application of an adhesive ophthalmic drug delivery device. The adhesive drug delivery device has been design to prevent the leakage of irrigation drugs and improve the patient comfort. (结膜囊冲洗为眼科护理操作的重要操作之一, 受水器是结膜囊冲洗的必备工具。本研究设计一种粘贴式眼科受水器, 可有效阻止冲洗液的外流, 患者使用舒适度高, 有助于提升护理人员工作效率。)